Early positive effects of tree species richness on soil organic carbon accumulation in a large-scale forest biodiversity experiment. (29th May 2019) - Li, Yin; Bruelheide, Helge; Scholten, Thomas; Schmid, Bernhard; Sun, Zhenkai; Zhang, Naili; Bu, Wensheng; Liu, Xiaojuan; Ma, Keping
Abstract: Aims: Tree species richness has been reported to have positive effects on aboveground biomass and productivity, but little is known about its effects on soil organic carbon (SOC) accumulation. Methods: To close this gap, we made use of a large biodiversity–ecosystem functioning experiment in subtropical China (BEF-China) and tested whether tree species richness enhanced SOC accumulation. In 2010 and 2015, vertically layered soil samples were taken to a depth of 30 cm from 57 plots ranging in tree species richness from one to eight species. Least squares-based linear models and analysis of variance were used to investigate tree diversity effects. Structural equation modeling was used to explore hypothesized indirect relationships between tree species richness, leaf-litter biomass, leaf-litter carbon content, fine-root biomass and SOC accumulation. Important Findings: Overall, SOC content decreased by 5.7 and 1.1 g C kg −1 in the top 0–5 and 5–10 cm soil depth, respectively, but increased by 1.0 and 1.5 g C kg −1 in the deeper 10–20 and 20–30 cm soil depth, respectively. Converting SOC content to SOC stocks using measures of soil bulk density showed that tree species richness did enhance SOC accumulation in the different soil depths. These effects could only to some extent be explained by leaf-litter biomass and not by fine-root biomass. Our findings suggest that carbon storage in new forests in China could be increased by planting more diverse stands, with the potential to contribute to mitigation of climate warming.